If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-16=2+3(t+2)
We move all terms to the left:
-16-(2+3(t+2))=0
We calculate terms in parentheses: -(2+3(t+2)), so:We get rid of parentheses
2+3(t+2)
determiningTheFunctionDomain 3(t+2)+2
We multiply parentheses
3t+6+2
We add all the numbers together, and all the variables
3t+8
Back to the equation:
-(3t+8)
-3t-8-16=0
We add all the numbers together, and all the variables
-3t-24=0
We move all terms containing t to the left, all other terms to the right
-3t=24
t=24/-3
t=-8
| 10x–3(2x–4)=8 | | 2(x+11)+4=34 | | Y-3=-(x-3) | | T-5(1/6x-8)=40-x-1/6x | | 2y^-4+5y^-2-3=0 | | 2x-30=-7(8x-4) | | k−–524=588 | | 104÷(104÷(x-5)-5)=x | | x+21=-42 | | –26y=–910 | | 47+31x=180 | | x((104÷(x-5))=104 | | 22x=-28 | | 1-11(x+8)=5+7x | | (6x-7)=(83-2x) | | -19=8-(j+23) | | (3x-34)=(2x+19) | | x(2x-6)-15=0 | | -2(v-4)+15=29 | | 44=4(q+11)-8 | | 8(z-4)+3=-93 | | n/n+n+n+n=16 | | (√3)^2x+4=243 | | 32=6+7a-5a | | -3(2x+5)-7=14 | | x/7+x/5=10 | | -8(-3k-5)=3k+19 | | -8(-3k-5)=k+19 | | t^2-20t-96=0 | | 20t+20=200 | | (5x-2)/2x=2 | | 2x-1=x^2-16x+64 |